Assessment of Direct Medical Cost of Hospitalized COVID-19 Adult Patients in Kuwait During the First Wave of the Pandemic - AlManie SA; AlHazami MS; Ebrahim A; Attique MS (ClinicoEconomics and Outcomes Research, 2024)
Sarah A AlManie,1 Mai S AlHazami,1 Alyah Ebrahim,2 Muhammad S Attique2 1Department of Pharmacy Practice, School of Pharmacy-Kuwait University, Kuwait City, Kuwait; 2Respiratory Department- Jaber Al-Ahmad Al-Sabah Hospital, Kuwait City, KuwaitCorrespondence: Sarah A AlManie, Email Sarah.almanie@ku.edu.kwObjective: This study aims to estimate the direct medical cost of COVID-19 hospitalizations and to utilize prevalence estimates from Jaber Al-Ahmad Hospital to estimate the direct medical cost of all hospitalized adult patients in Kuwait using a decision tree analysis.Methods: A cost-of-illness model was developed. The Ministry of Health perspective was considered, direct medical costs were estimated from July 1st to September 30th, using a bottom-up approach. The mean cost per hospitalized patient was estimated using a decision analysis model. Prevalence estimates of ambulance use, use of ER, ICU admission, and mortality were considered in the current study. Patients aged 18 years and above with a confirmed diagnosis of COVID-19 were included. One-way sensitivity analysis and probabilistic sensitivity analysis (PSA) were performed.Results: Data for 2986 patients were analyzed. The mean age was 61 (SD= 11) years old. Most of the patients were Kuwaiti (2864, 95.91%), and more than half were females (1677, 56.16%). Of the total hospital admissions, 417 patients (14%) were admitted to the ICU. The average length of the hospital stay was 11 (SD= 9) days, and among all hospital admissions, 270 (9.04%) patients died. The total estimated direct medical cost of hospitalized patients at Jaber Al-Ahmad Hospital was $47,213,768 (14,283,203.6 KD). The average cost of hospital stay per patient was estimated at $15,498 (4,688.60 KD). The weighted average cost per hospitalized patient in Kuwait was estimated at $16,373 (4,953.08 KD). The total direct medical cost of hospitalized COVID-19 patients in Kuwait during the study period was estimated at $174,372,450 (52,751,502 KD).Conclusion: The COVID-19 pandemic constituted a significant burden on the Kuwaiti healthcare system. The findings of this study urge the need for preventive care strategies to reduce adverse health outcomes and the economic impact of the pandemic.Keywords: economic impact, COVID-19, direct medical cost, cost analysis, Kuwait